2023
DOI: 10.1021/acs.chemrev.3c00169
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Experimental Advances in High-Pressure Behaviors of Nanoparticles

Lingyao Meng,
Tuan V. Vu,
Louise J. Criscenti
et al.

Abstract: Using compressive mechanical forces, such as pressure, to induce crystallographic phase transitions and mesostructural changes while modulating material properties in nanoparticles (NPs) is a unique way to discover new phase behaviors, create novel nanostructures, and study emerging properties that are difficult to achieve under conventional conditions. In recent decades, NPs of a plethora of chemical compositions, sizes, shapes, surface ligands, and self-assembled mesostructures have been studied under pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 417 publications
0
10
0
Order By: Relevance
“…As a result, octahedron translation was paired with the breaking of binding ligands, which likely led to the layer fragmentation into smaller parts and subsequent peak broadening. Additionally, higher pressure might induce a sintering process, leading to an increase in total entropy by disrupting the p 31 m symmetry and causing irreversible phase transition ( vide infra ). In stage IV, the fwhm continued to increase, albeit at a significantly slower rate, as pressure was released from 17.13 to 0.08 GPa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, octahedron translation was paired with the breaking of binding ligands, which likely led to the layer fragmentation into smaller parts and subsequent peak broadening. Additionally, higher pressure might induce a sintering process, leading to an increase in total entropy by disrupting the p 31 m symmetry and causing irreversible phase transition ( vide infra ). In stage IV, the fwhm continued to increase, albeit at a significantly slower rate, as pressure was released from 17.13 to 0.08 GPa.…”
Section: Resultsmentioning
confidence: 99%
“…Unveiling this random-layer superlattice not only expands the catalog of known self-assembled superlattice structures but also paves the way for innovative approaches in interpreting structural insights from small-angle X-ray scattering (SAXS) . This has potential implications for applications such as optical and electronic functionalities …”
Section: Introductionmentioning
confidence: 98%
“…Understanding the stability of the structure constitutes a crucial aspect in ascertaining the ideal design and applications of nanocrystals (NCs). The study of phase transitions under extreme conditions , has been instrumental in unraveling the fundamental properties and behaviors of various chalcogenide-based nanomaterials. High pressure can induce reversible or irreversible phase transformations in nanostructures as well as to lead to their morphological changes resulting in the synthesis of nanostructures with different morphologies such as nanowires from quasi-spherical NCs .…”
Section: Cer In Faceted Cdse Ncs Under Anaerobic Conditions With Cu(i...mentioning
confidence: 99%
“…The manipulation strategies of the local coordination environment consist mainly of chemical doping, temperature, and pressure regulation. Among these, the versatility of high-pressure technology in luminescence regulation has received extensive attention with its application in pressure sensing in recent years. Previous studies have demonstrated that Mn-based OIMHs are very promising materials, especially in the topics of pressure-induced enhancement and piezochroism. , Upon hydrostatic compression, the lattice distortion of Mn-based OIMHs could lead to a decrease in interatomic distances and variation of the band gaps. , This results in alterations of crystal field splitting energy, causing changes in high-pressure structures and optical properties like emission intensity and wavelength. , However, the instability of halide compounds upon compression would result in complicated phase transitions, which manifest as changes in optical properties. , This distorts the linear correlation between pressure and emission wavelength/intensity; for example, the self-trapped exciton emission is abruptly enhanced when reaching the pressure of a phase transition in CsCu 2 I 3 . In addition, the insensitivity and irreversibility of optical properties to pressure limit their applications.…”
Section: Introductionmentioning
confidence: 99%